Recovering of Dizziness of a Patient with Sinusitis after Root Canal Therapy for Upper Second Molar - Ibrahem Amro; Lyana Shawar; Raed abu Hantash; Basem Abuquba; Akram Amro (Case Reports in Dentistry)
This case report illustrates the recovery of dizziness of a young healthy patient after root canal therapy of upper second molar. The patient developed dizziness and unbalanced walking four months ago. After cardiac, ENT, neurological, physiotherapy and medical investigations, his entire checkup showed no abnormalities. The patient visited a dental clinic for a routine checkup; after dental clinical and radiographical examination, a chronic abscess infection in an upper second molar region close to the sinus was diagnosed. Root canal therapy was performed that resulted in a disappearance of the dizziness and full recovery was achieved. Conclusion. Infected upper teeth with periapical lesion are associated with dizziness as a complication of odontogenic-related sinusitis. Dental and medical cooperation contributes to a better management diagnosis of the dizziness.